Profitability and Sustainable Growth of Manufacturing Firms: Empirical Evidence from Malaysia and Indonesia - Wijaya, Liem Alfando; Atahau, Apriani Dorkas Rambu (Program Studi Akuntansi FPEB UPI, 2021)
This study aims to determine the effect of profitability on sustainable growth in Malaysian and Indonesian manufacturing firms. By using 58 Malaysia manufacturing firms and 90 Indonesia manufacturing firms that listed on Malaysia and Indonesia Stock Exchanges from 2016 until 2018, the findings show that the profitability of the firm significantly influences the firm's sustainable growth. Firm size as a moderating variable is also able to moderate the effect of profitability on sustainable growth. This research implies that manager in manufacturing firms may boost the profit to achieve sustainable growth. In addition, large scale firms need to optimize their total assets to increase their profit in order to create larger effect on sustainable growth.